Extensional Seismogenic Stress and Tectonic Movement on the Central Region of the Tibetan Plateau - Jiren Xu; Zhixin Zhao (International Journal of Geophysics)
Various earthquake fault types, mechanism solutions and stress fields, as well as GPS and geothermal data are analyzed for the study of the crustal movements on the Tibetan plateau and their tectonic implications. The results show that a lot of the normal faulting type-event concentrated at altitudes greater than 4000 m on the central Tibetan plateau. The altitudes concentrating normal faulting type-events can be zoned two parts: the western part, the Lhasa block, and the eastern part, the Qiangtang-Changdu region. The azimuths of T-axes are in a general E-W direction in the Lhasa block and NW-SE or NNW-SSE in the Qiangtang-Changdu region at the altitudes of the Tibetan plateau. The tensional stresses in E-W direction and NW-SE direction predominate normal faulting earthquake occurrence in the Lhasa block and the Qiangtang-Changdu region, respectively. The slipping displacements of the normal-faulting-type events have great components in near E-W direction and NW-SE direction in the Lhasa block and the Qiangtang-Changdu region, respectively. The extensions are probably an eastward or southeastward extensional motion, being mainly tectonic activity phenomena in the plateau altitudes. The extensional motions due to normal-fault earthquakes are important tectonic activity regimes on the high altitudes of the plateau. The easterly crustal extensions on the plateau are attributable to the gravitational collapse of the high plateau and eastward extrusion of hotter mantle materials beneath the eastern boundary of the plateau. Numbers of thrust-fault and strike-slip-fault earthquakes with strong compressive stress in a general NNE-SSW direction occur on the edges of the plateau.